CT-based screening of sarcopenia and its role in cachexia syndrome in pancreatic cancer - Khristenko, Ekaterina; Sinitsyn, Valentin; Rieden, Tatiana; Girod, Parker; Kauczor, Hans-Ulrich; Mayer, Philipp; Klauß, Miriam; Lyadov, Vladimir (PLOS ONE, 2024)
Since computed tomography (CT) is a part of standard diagnostic protocol in pancreatic ductal adenocarcinoma (PDAC), we have evaluated the value of CT for sarcopenia screening in patients with PDAC, intending to expand the diagnostic value of tomographic studies. In our study, we included 177 patients with available CT images. Two groups were formed: Group 1 consisted of 117 patients with PDAC in various locations and stages and Group 2, or the control group, consisted of 60 "nominally healthy" patients with other somatic non-oncological diseases. The body mass index (BMI) was defined as a ratio of patient's weight to the square of their height (kg/m2). CT-based body composition analysis was performed using commercially available software with evaluation of sarcopenia using skeletal muscle index (SMI, cm2/m2). Based on the SMI values, sarcopenia was found in 67.5% of patients (79 out of 117) in the first patient group. It was found more frequently in males (42 out of 56; 75%) than in females (37 out of 61; 60.6%). Additionally, we observed a decrease in muscle mass (hidden sarcopenia) in 79.7% in patients with a normal BMI. Even in overweight patients, sarcopenia was found in 50% (sarcopenic obesity). In patients with reduced BMI sarcopenia was found in all cases (100%). Statistically significant difference of SMI between two groups was revealed for both sexes (p = 0,0001), with no significant difference between groups in BMI. BMI is an inaccurate value for the assessment of body composition as it does not reflect in the details the human body structure. As SMI may correlate with the prognosis, decreased muscle mass- especially "hidden" sarcopenia or sarcopenic obesity- should be reported. The use of CT-based evaluation of sarcopenia and sarcopenic obesity will allow for a better treatment response assessment in patients with cancer cachexia.
Gesehen am 22.07.2024